2014
DOI: 10.11121/ijocta.01.2015.00205
|View full text |Cite
|
Sign up to set email alerts
|

On constrained reliability maximization using active redundancy in coherent systems with non-overlapping subsystems

Abstract: The paper investigates the problem of constrained reliability maximization by allocating redundancy and proposes how to solve it for a broad group of complex coherent systems. Redundancy is an effective engineering tool to enhance system reliability to make a system fail-safe. Since adding redundancy increases the cost and complexity of a system design, it should be used wisely. The work considers an exact solution to the problem under resource constraints and finds optimal redundancy numbers. The proposed met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 10 publications
(10 reference statements)
0
3
0
Order By: Relevance
“…The resultant agricultural nonpoint source pollutants were flushed into the rivers along with drainage and precipitation through field ditches, and finally rushed to Poyang Lake and affected the lake water quality. As a primary sewage interception channel in agricultural nonpoint source pollution control pathway, the ecological ditches have been investigated by many researchers [3][4][5][6][7][8] on their ability to intercept the nutrients. The research findings showed that the ditch sediments have a stronger nutrient-removing ability.…”
Section: Introductionmentioning
confidence: 99%
“…The resultant agricultural nonpoint source pollutants were flushed into the rivers along with drainage and precipitation through field ditches, and finally rushed to Poyang Lake and affected the lake water quality. As a primary sewage interception channel in agricultural nonpoint source pollution control pathway, the ecological ditches have been investigated by many researchers [3][4][5][6][7][8] on their ability to intercept the nutrients. The research findings showed that the ditch sediments have a stronger nutrient-removing ability.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, more and more scholars have begun to focus on and study the agile manufacturing system oriented job shop scheduling and dynamic scheduling [4][5][6][7][8]. Chao-Yong Zhang et al investigated the dynamic scheduling in the cases of delayed arrival, processing of raw materials and assembling, as well as adding the new jobs urgently [9].…”
Section: Introductionmentioning
confidence: 99%
“…The algorithm is not restricted to the problem that the inverse matrix of the transformation matrix does not exist; (c) The algorithm is based on the GPU. DirectX 11 Shader (compute shader) was used to make point conversion and distance comparison operations thanks to the powerful GPU's parallel computing capabilities [9,10]. Compared with the algorithm running on the CPU, Pick up speed is 2-3 times faster.…”
Section: Introductionmentioning
confidence: 99%